Clinical, pathological and molecular evaluations and CT scan screening of coenurosis (Coenurus cerebralis) in sheep and calves - Gazioglu, Abdullah; Simsek, Sami; Kizil, Omer; Ceribasi, Ali Osman; Kesik, Harun Kaya; Ahmed, Haroon (Brazilian Coll Veterinary Parasitology, 2017)
The aims of this study were to diagnose coenurosis by means of computerized tomography (CT) scan imaging and molecular characterization of the CO1 gene using the polymerase chain reaction (PCR). Sheep and calves were necropsied, and CT scans on the cephalic region were performed on the animals. Sections of brain tissue infected with parasites were then stained with hematoxylin and eosin for microscopic examination. Material collected from brain cysts was fixed in 70% ethanol. PCR amplification was carried out using the CO1 mitochondrial gene. A total of 60 calves and 80 sheep were examined clinically and, of these, 15 calves and 38 sheep showed signs of depression, with counterclockwise circling movements and altered head carriage. Four sheep and one calf were necropsied, and C. cerebralis cysts were detected in all of them. A hypodense cyst was monitored in the right cerebellar hemisphere on a CT scan on one sheep. A cyst was found in the left frontal lobe on a CT scan on one calf. Microscopically, C. cerebralis cysts were surrounded by a fibrous or epithelial wall that presented necrosis on cerebral sections of both the sheep and the cattle. The CO1-PCR assay yielded a 446 bp band, which was sequenced and phylogenetically analyzed: the results confirmed the presence of T. multiceps. This study reports the first use of CT imaging on naturally infected calves and sheep for diagnosing coenurosis.
Avalıação clínıca, patológica e molecular e tomografia computadorizada de cenurose (Coenurus cerebralis) em carneiros e bezerros
Keywords: Coenurus cerebralis; CT imaging; PCR; sheep; calf; Turkey